QK type spaces of analytic functions - Hasi Wulan; Jizhen Zhou (Journal of Function Spaces and Applications)
For a nondecreasing function K:[0,8)?[0,8) and 0<p<8, -2<q<8, we introduce QK(p,q), a QK type space of functions analytic in the unit disk and study the characterizations of QK(p,q). Necessary and sufficient conditions on K such that QK(p,q) become some known spaces are given.